The Roles of Race and Mental Health in the On-scene Outcomes of Public Mass Shootings - Franklin, Sarah (Race and social problems, 2024)
Mass shootings are most frequently committed by white men. Yet, these white perpetrators often do not meet the same fatal fate as Black people who have committed lesser crimes, particularly in the United States. Furthermore, Black people with mental health issues in such situations are more commonly met with lethal force. This study investigates if disparities exist in the likelihood of being apprehended, taking one’s own life, or being killed by police or others during a public mass shooting incident based on one’s race and known mental health status. Using the Violence Project data, this study aids understanding of the causes and consequences of mass violence.